Penerapan Perda Bukittinggi Nomor 2 Tahun 2024 tentang Ketertiban Umum terhadap LGBT Studi Kasus Kota Bukittinggi Ditinjau dari Fiqih Siyasah Tanfidziyah - Faulah Ramashur; Ali Rahman (AHKAM, 2026)
Increasing public attention to the LGBT phenomenon in Bukittinggi City, which is perceived as inconsistent with religious values, Minangkabau customs, and social norms, provides an important basis for strengthening public order policy through Bukittinggi City Regional Regulation Number 2 of 2024. This study aims to analyze the implementation of this regional regulation regarding LGBT activities and to examine it from the perspective of Fiqih Siyasah Tanfidziyah. This study used a qualitative method with an empirical juridical approach. Data were collected through observation, interviews with Satpol PP, LKAAM, MUI, Bundo Kanduang, and the community, as well as documentation. The results show that the implementation of the regional regulation is carried out through supervision, enforcement, socialization, and guidance using persuasive, educational, and religious approaches. The implementation of this policy is supported by synergy among the local government, customary institutions, religious leaders, and the community, but it still faces obstacles in the form of leaked information about raids, suboptimal effectiveness of sanctions, the influence of social media, and low public awareness. From the perspective of Fiqih Siyasah Tanfidziyah, the implementation of the regional regulation reflects the government’s function in realizing public welfare and maintaining public order in accordance with the principles of Islamic law. The conclusion of this study emphasizes that the effectiveness of the implementation of Bukittinggi City Regional Regulation Number 2 of 2024 requires strengthened inter-institutional coordination, increased socialization, and continuous guidance so that social order and public welfare can be realized more optimally.